The Effect of Client-Centered Counseling on Elementary Students’ Self-Regulated Linguistic Ability - Seidi, Ali; Nazari, Hosna; Ardeshiri, Hediyeh; Esmaeili , Soheil; Karimi, Sara; Bijanpoor, Hasti (Iranian Journal of Neurodevelopmental Disorders, 2026)
Purpose: The present study aimed to investigate the effectiveness of a client-centered counseling intervention in improving self-regulated linguistic ability among elementary school students.Methods and Materials: This study employed a quasi-experimental design with a pretest–posttest–follow-up structure and a control group. The sample consisted of 60 elementary students aged 9–11 years from Kermanshah, Iran, who were selected through convenience sampling and assigned to experimental and control groups using matched-pair randomization. The experimental group participated in 12 weekly sessions of client-centered counseling based on Rogerian principles, while the control group continued regular classroom activities. Data were collected using the Self-Regulated Linguistic Ability Scale (SRLAS), an observational checklist of linguistic behaviors, language sample analysis (including mean length of utterance, lexical diversity, and self-corrections), and teacher ratings of academic language performance. Data were analyzed using mixed-design ANOVA and MANOVA to examine group, time, and interaction effects, along with effect size calculations and post hoc comparisons.Findings: The results revealed significant group × time interaction effects for overall self-regulated linguistic ability and all subcomponents, with large effect sizes (η² ranging from 0.22 to 0.42). The experimental group demonstrated statistically significant improvements from pretest to posttest (p < .001) and maintained these gains at follow-up, whereas the control group showed no significant changes. Posttest comparisons indicated significant differences between groups in favor of the experimental condition (p < .001, Cohen’s d > 1.00). Additionally, multivariate analyses confirmed significant improvements in linguistic performance indicators, including mean length of utterance, lexical diversity, and frequency of self-corrections.Conclusion: The findings indicate that client-centered counseling is a highly effective intervention for enhancing self-regulated linguistic ability in elementary students, promoting both metacognitive and behavioral aspects of language use, with sustained effects over time.